Design of secondary controllers for microgrids with the consideration of communication issues - Lian, Zhijie (Nanyang Technological University, 2023)
With the increasing concerns about environmental problems, microgrid (MG) deployments throughout the world have increased. Traditionally, a hierarchical control method is applied to MG systems to guarantee safe and economical operation, which is divided into three layers, i.e., primary, secondary, and tertiary layers. The secondary control is usually realized in a centralized or distributed way, which relies on real-time signal transmissions through the communication channels. Controlled by such communication-assisted cooperative controllers, an MG is regarded as a coupled cyber-physical system (CPS). For such a CPS, communication issues, e.g., time delays and cyber attacks, are of significance as they could pose a dramatic threat to an MG's stable and secure operation. In order to solve the above drawbacks, advanced distributed and decentralized secondary control methods are proposed in MGs in this thesis.